Effects of Intermittent Theta Burst Stimulation Combined with Motor Imagery-Based Brain Computer Interface Training on Hand Function after Stroke - LIAN Yawen; LI Yinghua; LI He; JING Yuling; XU Guoxing; XIE Xixi; ZHENG Mengyao; MA Shuang; LI Zhenlan (康复学报)
ObjectiveTo investigate the clinical effect of intermittent theta burst stimulation (iTBS) combined with motor imagery-based brain computer interface (MI-BCI) training on hand function recovery after stroke.MethodsThe clinical data of 96 patients with post-stroke hand dysfunction who were hospitalized in the First Hospital of Jilin University from October 2023 to October 2024周ere retrospectively analyzed. According to the the actual treatment measures received by the subjects, they were divided into the conventional group (25 cases), iTBS group (28 cases), MI-BCI group (21 cases) and combined group (22 cases). All four groups received conventional rehabilitation treatment for 40 min/time. In addition, the iTBS group received iTBS training (192s/time); MI-BCI group received MI-BCI training (20min/time); The combined group received both iTBS training (192s/time) and MI-BCI training (20min/time). All treatments were provided once daily, 6 days/week for 4周eeks. Before and after the treatment, the Fugl-Meyer Assessment for Upper Extremity (FMA-UE) and its subscales for shoulder/elbow, wrist/hand and coordination were used to evaluate the upper limb motor function of the patients. The Brunnstrom recovery stages of hand (BRS-H) was used to evaluate the functional stage of the patient's hemiplegic limb. The Modified Ashworth Scale (MAS) was used to evaluate the muscle tone of the patients' hemiplegic fingers. The activities of daily living of the patients were evaluated by using the Barthel Index (BI) scale. The safety of this study was evaluated and the effect sizes of the four treatment methods were calculated for primary outcome measures.ResultsCompared with before treatment, the FMA-UE shoulder/elbow, wrist/hand subscale scores and total score in the 4 groups increased after 4周eeks of treatment (P<0.05). The FMA-UE coordination subscale scores in the MI-BCI group and the combined group increased compared with that before treatment (P<0.05). After 4周eeks of treatment, compared with the conventional group, the FMA-UE shoulder/elbow and wrist/hand subscale scores and the total score in the combined group were higher (P<0.0083). Compared with the iTBS group, the FMA-UE shoulder/elbow subscale score and the total score in the combined group were higher (P<0.0083). Pairwise comparisons of the score differences between groups showed that compared with the conventional group, the combined group had greater improvements in the FMA-UE shoulder/elbow, wrist/hand subscale scores and the total score (P<0.0083). Compared with the iTBS group and the MI-BCI group, the combined group had greater improvements in the FMA-UE shoulder/elbow subscale scores and the total score (P<0.0083). Compared with before treatment, the BRS-H scores in 4 groups all increased after 4周eeks (P<0.05). Pairwise comparisons of the score differences between groups showed that, compared with the conventional group and the iTBS group, the combined group had greater improvements in BRS-H scores (P>0.0083). Compared with before treatment, the MAS score of the iTBS group increased after 4周eeks (P<0.05), while no statistically significant differences were observed in the conventional group, the MI-BCI group and the combined group (P>0.05). After 4周eeks of treatment, there was no statistically significant between-group differences in MAS score changes among the 4 groups (P>0.0083). Compared with before treatment, the BI scores of all 4 groups increased after 4周eeks (P<0.05). After 4周eeks of treatment, compared with the conventional group, the iTBS group and the MI-BCI group, the BI scores in the combined group was higher (P<0.0083). Pairwise comparisons of the score differences between groups showed that, compared with the conventional group and the MI-BCI group, the combined group showed greater BI score improvements (P<0.0083). Safety evaluation showed minimal adverse events reported by the 4 groups during the treatment process, demonstrating good safety. After 4周eeks of treatment, the FMA-UE shoulder/elbow subscale and total score, BRS-H score and BI score in the 4 groups showed large effect sizes. The FMA-UE wrist/hand subscale showed a moderate effect size ranging from 0.059 to 0.138. The FMA-UE coordination subscale and MAS score showed small effect sizes ranging from 0.010 to 0.059.ConclusioniTBS combined with MI-BCI training can improve the hand motor function and the activities of daily living in stroke patients.